FRI0041 The JAK Inhibitor (Tofacitinib) Inhibits TNF-Induced Gliostatin/thymidine Phosphorylase Expression in Human Fibroblast-like Synoviocytes. (15th July 2016) - Kawaguchi, Y.; Waguri-Nagaya, Y.; Ikuta, K.; Tatematsu, N.; Kobayashi, M.; Goto, H.; Nozaki, M.; Asai, K.; Otsuka, T.
Abstract : Background: The JAK/STAT signaling pathways mediate the effects of many cytokines and growth factors related rheumatoid arthritis (RA). Tofacitinib is a novel oral JAK inhibitor and it has demonstrated high efficacy in RA, even in non-responder to anti-TNF treatment. Gliostatin/thymidine phosphorylase (GLS/TP) is known to have angiogenic and arthritogenic activities. GLS/TP was expressed in inflamed synovial tissues of patients with RA. In cultured fibroblast-like synoviocytes (FLSs), GLS/TP expression was found to be up-regulated by inflammatory cytokines, such as IL-1β, TNFα. GLS acted as a cytokine in FLSs, augmenting its own synthesis, and also induced the extracellular secretion of matrix metalloproteinase (MMP)-1, and MMP-3. Therefore the suppression of GLS production might be an effective therapy in RA. Tofacitinib inhibits the function of T cells, however the mechanism of the action of tofacitinib had not been determined in fibroblast- like synoviocytes. Objectives: The purpose of this study was to investigate the effect of tofacitinib on GLS production in FLSs derived from patients with RA (RAFLSs). Methods: RAFLSs were cultured and stimulated by tumor necrosis factor (TNF)-α with or without treatment of tofacitinib. The expression levels of GLS were determined using reverse transcription-polymerase chain reaction (RT-PCR), enzyme immunoassay and immunocytochemistry. Results: In cultured RAFLSs, GLS mRNA and protein levels were significantly induced by stimulation with TNFα alone and these GLS/TP inductions were significantly suppressed by treatment of tofacitinib in a dose-dependent manner. Conclusions: Our data demonstrated that JAK/STAT activation play a pivotal role in TNF mediated GLS up-regulation in RAFLSs. Suppression of GLS production in inflamed synovia has been suggested as one of the anti-inflammatory effects of tofacitinib. References: Waguri Y, et al. Gliostatin/platelet-derived endothelial cell growth factor as a clinical marker of rheumatoid arthritis and its regulation in fibroblast like synoviocytes. Br J Rheumatol. 1997;36:315–321. Yamagami T, et al. FK506 inhibition of gliostatin/thymidine phosphorylase production induced by tumor necrosis factor-α in rheumatoid fibroblast-like synoviocytes. Rheumatol Int 2011; 31:903–909. Ikuta K, et al. The Sp1 transcription factor is essential for the expression of gliostatin/thymidine phosphorylase in rheumatoid fibroblast-like synoviocytes. Arthritis Research & Therapy 2012; 14:R87. Acknowledgement: This research was spportded by Grand-in-Aid for Scientific Research (C) (26462309) from the Japan Society for the Promotion of Science. Disclosure of Interest: Y. Kawaguchi: None declared, Y. Waguri-Nagaya Grant/research support from: Biomet Japan, Inc, Chugai Pharmaceutical Co., Ltd., Astellas Pharma Inc., Merck Sharp & Dohme Co., AbbVie Japan Co., Ltd., Ono Pharmaceutical Co., Ltd., K. Ikuta: None declared, N. Tatematsu: None declared, M. Kobayashi: None declared, H. Goto: None declared, M. Nozaki: None declared, K. Asai: None declared, T. Otsuka: None declared